Caudally pronounced deficiencies in preplate splitting and migration underly a rostro-caudal progression of cortical lamination defects in the reeler brain - Moreno, Nieves Mingo; Truschow, Pavel; Staiger, Jochen F.; Wagener, Jan Robin (Cerebral cortex, 2024)
In mammalian neocortex development, every cohort of newborn neurons is guided toward the marginal zone, leading to an “inside-out” organization of the 6 neocortical layers. This migratory pattern is regulated by the extracellular glycoprotein Reelin. The reeler mouse shows a homozygous mutation of the reelin gene. Using RNA in situ hybridization we could demonstrate that the Reelin-deficient mouse cortex (male and female) displays an increasing lamination defect along the rostro-caudal axis that is characterized by strong cellular intermingling, but roughly reproduces the “inside-out” pattern in rostral cortex, while caudal cortex shows a relative inversion of neuronal positioning (“outside-in”). We found that in development of the reeler cortex, preplate-splitting is also defective with an increasing severity along the rostro-caudal axis. This leads to a misplacement of subplate neurons that are crucial for a switch in migration mode within the cortical plate. Using Flash Tag labeling and nucleoside analog pulse-chasing, we found an according migration defect within the cortical plate, again with a progressive severity along the rostro-caudal axis. Thus, loss of one key player in neocortical development leads to highly area-specific (caudally pronounced) developmental deficiencies that result in multiple roughly opposite rostral versus caudal adult neocortical phenotypes.